SUSTAINABLE ENGINEERING SOLUTIONS FOR URBAN MOBILITY: DESIGNING SMART CITIES WITH AUTONOMOUS VEHICLES AND IOT - Prof. Paolo Bianchi (Modern American Journals, 2025)
The rapid urbanization of global populations and the increasing demand for efficient transportation systems are creating significant challenges for urban mobility. Sustainable engineering solutions, particularly those incorporating Autonomous Vehicles (AVs) and the Internet of Things (IoT), offer transformative potential for designing smarter and more sustainable cities. These technologies not only have the potential to reduce traffic congestion and pollution but also improve energy efficiency and enhance the quality of life in urban environments. This paper explores the integration of autonomous vehicles and IoT systems into urban mobility frameworks, focusing on the design of smart cities. By examining case studies, technological advancements, and the role of AI and data analytics, the paper highlights how these innovations can create sustainable, efficient, and inclusive urban transportation systems. The findings suggest that while there are substantial challenges, including infrastructure adaptation and policy development, these technologies offer a pathway toward more sustainable urban mobility solutions.
Keywords: Sustainable Engineering, Urban Mobility, Smart Cities, Autonomous Vehicles, Internet of Things (IoT), Urban Transportation, Smart Infrastructure, Traffic Management, Electric Vehicles, Sustainability.